Using magnetoelectric effect to reveal magnetization behavior of bulk and heavy ferromagnetic materials. (June 2021) - Yu, Zhonghui; Cao, Jiawei; Chu, Zhaoqiang; Asl, Mohammad Javad Pourhosseini; Yang, Jikun; Wang, Zehuan; Zhang, Hongkang; Li, Qunyang; Dong, Shuxiang
Highlights: Traditionally, magnetization performance of bulk ferromagnetic materials is evaluated mainly based on Faraday's law of electromagnetic induction, magneto-optical effect, superconducting quantum interference devices (SQUID, only for small specimen), etc. Here, we report that the magnetoelectric (ME) coupling effect of a composited Terfenol-D alloy/PMN-PT single crystal can be used to reveal magnetization behavior of an approaching bulk ferromagnetic material other than a small specimen. For the first time, we observed a perfect butterfly-shaped hysteresis loop of ME voltage (VME) versus DC magnetic field (Hdc) accompanying with a 180º phase change in Terfenol-D/PMN-PT composite when a bulk, high-μ magnetic material is approaching. It is further found that the required DC magnetic field for domain switching in Terfenol-D alloy could be notably decreased from hundreds oe to only 10 Oe once a high- μ permalloy is approached. Abstract: Traditionally, magnetization performance of bulk ferromagnetic materials is evaluated mainly based on Faraday's law of electromagnetic induction, magneto-optical effect, Superconducting Quantum Interference Devices (SQUID, only for small specimen), etc. Here, we report that the magnetoelectric (ME) coupling effect from a composited Terfenol-D alloy/PMN-PT single crystal under a constant-amplitude AC magnetic field excitation ( H ac  = 0.25 Oe at 1 kHz) can be used to reveal magnetization behavior of an approaching bulk ferromagnetic material. Investigations show that the magnetostriction λ33, m, piezomagnetic coefficient d33, m, ME voltage ( VME ) response spectrum of the ME composite have a strong dependence on the external ferromagnetic material. It is further found that the required DC magnetic field for domain switching in Terfenol-D alloy could be notably decreased from hundreds Oe to only 10 Oe once a high- μ permalloy is approached. This work shows that the ME composite has the potential to quickly, qualitatively evaluate the magnetization ( M ) or permeability ( μ) behavior of an approaching bulk and heavy ferromagnetic material or alloy via ME effect. Graphical abstract: Image, graphical abstract